Estudo de viabilidade técnica da utilização da ACBC e do RCC na composição de concretos - Moretti, Juliana Petermann (2014)
The civil construction is responsible for generating a lot of waste and the lack suitable for waste treatment can cause many environmental and social problems. Brazil is the world s largest producer in the sugar and alcohol sector. During the processing of sugarcane is generated the ash sand of the sugarcane bagasse (ASSB), resulting from the burning of bagasse in boilers. The ASSB is usually released in the environment inappropriately. This study aimed to verify the possibility of using the ASSB to partially replace river sand and the construction waste (CW) to partially replace crushed stone in concretes. The ASSB samples were standardized by manual sieving and deagglomeration. The CW samples were standardized by manual screening and automated screening. The ASSB and CW were subjected to physical and chemical characterization, by its chemical composition, sieve analysis, powdery material, absorption, bulk density and true density. The ASSB was used in concretes with 30% substitute level and the CW was used with 30%, 50% and 100% substitution levels, it were produced seven concretes recipe (REF, 30ASSB, 30CW, 50CW, 30ASSB30CW, 30ASSB50CW and 100CW). The concretes were submitted to tests of compressive and tensile strength, elastic modulus, void index, absorption, density and carbonation. The concretes produced with the isolated use of 30 % of ASSB (30ASSB) and 30 % and 50 % of CW (30CW and 50CW) presented similar mechanical properties to the reference concrete. The concretes produced with 30% of ASSB and 30% and 50 % of CW ( 30ASSB30CW, 30ASSB50CW) presented similar progression of carbonation to the reference concrete, however, the combined use of the ASSB and CW resulted in the achievement of concrete with a reduction of 17%, 12% and 8% in compressive strength at 7, 28 and 91 days, respectively. Thus it is possible to indicate the combined use of the ASSB and the CW as a partial substitute natural aggregates in concrete, since the decrease in resistance can be considered low against the possibilities of using concrete containing these wastes.